Utilizing Space Syntax Techniques to Understand the Relationship Between Spatial Configuration and Walkability in Urban Neighborhoods (Case Study: Valiasr Neighborhood, Tehran) - Shakibamanesh, Amir; Karimian, Bahar (Urban Planning and Construction, 2024)
The numerous benefits of walking, as one of the healthiest, simplest, and most cost-effective modes of transportation, have prompted many urban researchers to identify influential factors in pedestrian-oriented urbanism. These efforts aim to transform urban areas, including neighborhoods, into conducive environments for walking, thereby realizing related benefits such as sustainable development. Extensive research has confirmed the role of the built environment in attracting and distributing pedestrian movement, with a significant portion highlighting the relationship between urban configuration and walkability. This study aims to determine the role of urban configuration components in enhancing walkability at the neighborhood scale, selecting the Valiasr neighborhood in Tehran due to its location in the city’s commercial center with a high volume of pedestrian traffic. For this purpose, after identifying spatial configuration components related to walkability – including accessibility, connectivity, and spatial arrangement components – key streets in the neighborhood’s spatial configuration were identified using an initial analysis of spatial arrangement variables, followed by a survey of pedestrian volumes on selected streets. The evaluation of configuration components led to design recommendations in two layout patterns – grid and parallel block. The relationship between urban configuration and walkability, utilizing space syntax techniques, was identified after analyzing spatial arrangement variables in three different scenarios (existing condition and two proposed alternatives). The results indicate that accessibility components have the most significant impact on walkability in the Valiasr neighborhood. Following this, connectivity components were identified as influential in promoting pedestrian-oriented urbanism. Regarding spatial arrangement components, a comparison with prior research confirms that spatial elements do not operate independently of mixed-use and access to services and facilities. Instead, they play a role not in the formation of movement but in facilitating and directing it.